PEDAGOGICAL PRINCIPLES OF USING THE MUSICAL AXIOLOGICAL APPROACH IN MODERN HIGHER EDUCATION (Scientific journal of the Fergana State University, 2024)
This article deals with the pedagogical foundations of the study of the Uzbek national musical heritage and the development of related knowledge based on axiological values. The purpose of this article is to highlight the importance, effectiveness, possibilities and necessity of using an axiological approach in modern music education. In this sense, it is necessary to consider the content, classification and methods of the axiological approach in the pedagogical process.